Emojis and Courtesy: the WhatsApp Case - Gutierrez Jimenez, Jorge Armando (2021)
The following work studies the emoji as a distinctive of politeness in messages issued by a WhatsApp group. During the study, 20 members of a private WhatsApp group called Parceros participated, ranging in age from 25 to 50 years old, made up of men and women, statements broadcast by chat were taken in random order, and the different types of politeness based on the categorization made by Bernal (2007) were also taken into account. The research was done under the qualitative method and discursive character. The research concludes that the emoji is used in a dynamic way among the participants, connoting from the emotional, to activities related to politeness.